2004
DOI: 10.1111/j.1745-7599.2004.tb00430.x
|View full text |Cite
|
Sign up to set email alerts
|

Intimate‐Partner Violence: A Retrospective Review of Records in Primary Care Settings

Abstract: Practitioners should develop a common area for documenting reports of IPV. The level and depth of resources available within the setting and the community may affect providers' willingness to screen for IPV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
1
18
1
Order By: Relevance
“…Reported rates of IPV vary widely from one cultural group to another (CDC, National Center for Injury Prevention and Control, 2011;Magnussen et al, 2004;Magnussen, Shoultz, Hansen, Sapolu, & Samifua, 2008;Shoultz et al, 2007Shoultz et al, , 2010; however, there are little data available regarding the incidence and prevalence of IPV among women who are members of a variety of cultural groups (Samuel, 2003;Senturia, Sullivan, Ciske, & ShiuThornton, 2000). Although women of Asian and Pacific Islander (API) backgrounds report a lower rate of IPV than other cultural groups (Tjaden & Thoennes, 2000), researchers who work with these women have estimated that the prevalence of IPV is as high in API populations as in other groups and call for further investigation to ascertain the extent to which this phenomenon can be explained by the level of willingness to disclose abuse by members of these groups.…”
Section: Issues Of Categorization Of Cultural Groupsmentioning
confidence: 96%
See 1 more Smart Citation
“…Reported rates of IPV vary widely from one cultural group to another (CDC, National Center for Injury Prevention and Control, 2011;Magnussen et al, 2004;Magnussen, Shoultz, Hansen, Sapolu, & Samifua, 2008;Shoultz et al, 2007Shoultz et al, , 2010; however, there are little data available regarding the incidence and prevalence of IPV among women who are members of a variety of cultural groups (Samuel, 2003;Senturia, Sullivan, Ciske, & ShiuThornton, 2000). Although women of Asian and Pacific Islander (API) backgrounds report a lower rate of IPV than other cultural groups (Tjaden & Thoennes, 2000), researchers who work with these women have estimated that the prevalence of IPV is as high in API populations as in other groups and call for further investigation to ascertain the extent to which this phenomenon can be explained by the level of willingness to disclose abuse by members of these groups.…”
Section: Issues Of Categorization Of Cultural Groupsmentioning
confidence: 96%
“…In 2006, 22,000 adults in Hawaii reported IPV, 3% of the adult population, and 10% of high school students reported being physically injured by a partner (SMS Research and Marketing Service, Inc., 2006). Although there are no prevalence data currently available specific to Native Hawaiians or Pilipinos 2 , a retrospective study performed in 2004 (Magnussen et al, 2004) found that out of a total valid sample of 337 records reviewed at four community health centers, 31 or 9% of the records reported IPV. The percentage of Native Hawaiian women who reported IPV was the highest of any group (32%); however, they represented only 19% of the total population reviewed.…”
Section: Introductionmentioning
confidence: 97%
“…Unfortunately, screening and disclosure rates remain low; existing studies on disclosure indicate that only 5 % to 15 % of women have disclosed abuse to their providers [39][40][41]. Survivors' preferences not to be pressured to disclose [42][43][44] and health provider discomfort with discussing IPV [45][46][47] compound the difficulties in identifying and supporting survivors [34,44,[48][49][50][51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…Conceptions of IPV and risk appraisal for future victimization can differ dramatically between clinicians and women who experience IPV (Cattaneo, 2007). Furthermore, professionals from different disciplines have different perspectives, and there are few clear guidelines for intervention within disciplines (Magnussen et al, 2004;Tower, 2003Tower, , 2006Wandrei & Rupert, 2000). variables that are consistent with Bandura's (1977) observational/modeling theory.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…While clinicians and women who experience IPV (Cattaneo, 2007). Furthermore, professionals from different disciplines have different perspectives, and there are few clear guidelines for intervention among disciplines (Magnussen et al, 2004;Tower, 2003Tower, , 2006Wandrei & Rupert, 2000).…”
Section: Importance Of the Knowledge Gainedmentioning
confidence: 99%